Computer-Aided Design, Modeling and Simulation of a New Solar Still Design. (20th July 2011) - Li Li, Jeremy (Zheng) Jeremy (Zheng)
Abstract : The clean and pure drinking water is important in today's life but current water sources are usually brackish with bacteria that cannot be used for drinking. About 78% of water available in the sea is salty, 21% of water is brackish, and only 1% of water is fresh. Distillation is one of the feasible processes applied to water purification, and it requires the energy inputs, such as solar radiation. Water is evaporated in this distillation process and water vapor can be separated and condensed to pure water. Now, with the change from conventional fuels to renewable and environment friendly fuels sources, the modern technology allows to use the abundant energy from the sun. It is better to use solar energy to process the water desalination since it is more economical than the use of conventional energies. The main focus of this paper is applying computer-aided modeling and simulation to design a less complex solar water distillation system. The prototype of this solar still system is also built to verify its feasibility, functionality, and reliability. The computational simulation and prototype testing show the reliability and proper functionality of this solar water distillation system.